Acceptability of donor funding for clinical trials in the UK: a qualitative empirical ethics study using focus groups to elicit the views of research patient public involvement group members, research ethics committee chairs and clinical researchers. Issue 6 (17th June 2022) - Shearman, Kirstie; Masters, Alexander; Nutt, Dominic; Bowman, Simon; Draper, Heather
Abstract : Objectives: The Plutocratic Proposal is a novel method of funding early phase clinical trials where a single donor funds the entire trial and in so doing secures a place on it. The aim of this study was to identify and explore concerns that may be raised by UK research ethics committees (RECs) when reviewing clinical trials funded in this way. Design: Empirical ethics combining ethical analysis and qualitative data from three focus groups held online using Frith's symbiotic approach. Data were analysed using inductive thematic approach informed by the study aims and ethical analysis. Participants: 22 participants were recruited: 8 research patient public involvement group members, 7 REC chairs and 7 clinical researchers. All were based in the UK. Results: With one exception, participants thought the Plutocratic Proposal may be 'all things considered' acceptable, providing their concerns were met, primary of which was upholding scientific integrity. Other concerns discussed related to the acceptability of the donor securing a place on the trial including: whether this was an unfair distribution of benefits, disclosing the identity of the donor as the funder, protecting the donor from exploitation and funding a single study with multiple donors on the same terms. Some misgivings fell outside the usual REC purview: detrimental impact of donors of bad character, establishing the trustworthiness of the matching agency and its processes and optimising research funding and resources. Despite their concerns, participants recognised that because the donor funds the whole trial, others would also potentially benefit from participating. Conclusions: We identified concerns about the Plutocratic Proposal. UK RECs may be open to approving studies if these can be addressed. Existing governance processes will do some of this work, but additional REC guidance, particularly in relation to donors securing a place on the trial, may be necessary to help RECs navigate ethical concerns consistently.